Revelation of an enigmatic signaling machinery—First insights into the mammalian TRPC architecture. (September 2018) - Groschner, Klaus; Tiapko, Oleksandra
Graphical abstract: Highlights: Transient receptor potential canonical (TRPC) channel structures are discussed. Information from cryo-EM analysis and previous homology modeling are compared. Future directions of TRPC resarch are highlighted. Abstract: Canonical TRP channels (TRPCs) are a particularly enigmatic family of signaling molecules with multimodal sensing features, being involved in a wide range of biological functions. Until very recently, the main hurdle towards comprehensive mechanistic understanding of TRPC signaling has been the lack of structural information. This has changed early this year by several reports on TRPC architectures resolved by single particle cryo-EM analysis. These studies confirmed recently elaborated concepts on TRPC structure-function relations, and unveiled unanticipated features and complexity in the TRPC sensing machinery.